The study of apoptotic cells by flow cytometry - Ormerod, MG (Leukemia, 1998)
Programmed cell death (PCD) is of fundamental importance in the normal development of an animal. It also plays a key role in tumour and radiation biology. PCD produces a sequence of changes occurring in cells called apoptosis. The main elements of this apoptotic cascade are rapidly being elucidated. Flow cytometry has been used to follow many of these changes. It has also been used to quantify the number of apoptotic cells in a culture and, more recently, in clinical samples. In this review, the properties of apoptotic cells and the main features of the apoptotic cascade are described. How flow cytometry can be used to follow changes during the apoptotic cascade is then discussed.